Assessment of cardiovascular regulation during head-up tilt and suspension in swimmers - Ifuku, H.; Shiraishi, Y. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of the present study was to compare cardiovascular responses in competitive swimmers with those in track and field (T and F) athletes during head-up tilt with engagement of the antigravity muscles in the lower extremities and during passive head-up suspension without the engagement of the antigravity muscles. METHODS: Blood pressure and heart rate during head-up tilt were compared among T and F athletes (N = 11), competitive swimmers (N = 15), and untrained subjects (N = 11). Moreover, stroke volume, cardiac output, and total peripheral resistance during head-up tilt and head-up suspension were also measured in T and F athletes and competitive swimmers. RESULTS: The heart rate increased significantly in all subject groups during head-up tilt; however, the MBP decreased in untrained subjects but did not change significantly in T and F athletes or competitive swimmers. Moreover, the DBP did not change significantly in untrained subjects or T and F athletes but increased significantly in swimmers. As with the head-up tilt, during the head-up suspension, the SBP decreased significantly and the heart rate increased significantly in both types of athletes, though the MBP decreased significantly. The ratios of decrease in stroke volume and cardiac output were significantly larger in swimmers than in T and F athletes during head-up tilt, but no significant difference was noted during head-up suspension. In T and F athletes, the ratios of decrease in stroke volume and cardiac output were significantly larger during head-up suspension than during head-up tilt, but no significant difference was noted in swimmers. CONCLUSION: The action of the antigravity muscles on cardiovascular regulation during upright standing is smaller in competitive swimmers than in T and F athletes.